Design of an Arduino Uno-Based Garden Security System for Corn from Pests Using RTC as a Timer - Sriwati Sriwati; Musrawati Musrawati; Andi Haslinda (Pelopor Publikasi Akademika, 2023)
This study aims as a security system for corn plants from Arduino-based pests using a DC to AC inverter with a 220V output as the output, and designing the Arduino Uno microcontroller system to work automatically by using the RTC as a timer, aims to make it easier for corn farmers to operate this equipment. Swine pests are a serious threat to farmers because they can cause crop failure, many farmers are already bothered by the presence of pig pests. The results of this study are a 12 Volt 6 AH battery as a voltage source to provide voltage to the Arduino Uno microcontroller, RTC relay, and inverter circuit as output. The RTC sensor is used as a timer, which disconnects and connects the battery current to the inverter using a 5v dc relay. This tool works at night for 12 hours, from 18.00 to 06.00 in the morning, and from 06.01 to 18.01 the RTC module will actively give a signal to the relay to connect and disconnect the battery voltage current to the inverter. With this tool, it makes it easier for farmers to monitor the safety of the garden corn plants from pests, and no longer need to go to the garden at night for manual installation.